Effect on the electrical and morphological properties of Bi incorporation into ZnO:Ga and ZnO:Al thin films deposited by confocal magnetron sputtering. (June 2018) - Correia, F.C.; Salvador, P.B.; Ribeiro, J.M.; Mendes, A.; Tavares, C.J.
Abstract: This paper reports the effect on the electrical and morphological properties of co-doping ZnO thin films with Bi and Al or Ga. To do so, a confocal sputtering geometry was used with a Bi target and two intrinsically doped ZnO:Ga and ZnO:Al targets. By depositing at an intentional heating of 200 °C and applying a post-deposition thermal treatment at 350 °C and 300 °C, for ZnO:Ga, Bi and ZnO:Al, Bi, respectively, electrical resistivity values of 1.3 × 10 −3 Ω cm and 4.8 × 10 −4 Ω cm were achieved, with an optical transmittance above 80%. The X-ray diffraction data shows that all doped ZnO films have a wurtzite hexagonal structure with preferential crystal growth perpendicular to the (002) plane. The Seebeck coefficient was measured for the ZnO:Al, Bi films, where a maximum value of −48 μV K −1 was registered. The optimized electrical properties were correlated with the preferential crystalline texture along [001] and the corresponding current density applied to the Bi dopant target, J(Bi). ZnO:Al, Bi films present out-of-plane compression stress, which concomitantly increases with J(Bi), due to higher compact volume of unit cell with lower lattice parameter c when compared with the undoped ZnO. By controlling the incorporation of Bi, the deposition temperature and the post-deposition thermal treatment temperature, improvements on the thermoelectric power factor of ZnO:Ga and ZnO:Al thin films can be achieved. Highlights: ZnO:Ga, Bi and ZnO:Al, Bi thermoelectric thin films. Enhancement of power factor with Bi doping. Highest electrical conductivity and power factor correlated with enhancement in film crystallinity.